2021
DOI: 10.1128/mbio.00294-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV/HAART and Other Clinical Variables on the Oral Mycobiome Using Multivariate Analyses

Abstract: The oral microbiome is considered an important factor in health and disease. We recently reported significant effects of HIV and several other clinical variables on the oral bacterial communities in a large cohort of HIV-positive and -negative individuals. The purpose of the present study was to similarly analyze the oral mycobiome in the same cohort. To identify fungi, the internal transcribed spacer 2 (ITS2) of the fungal rRNA genes was sequenced using oral rinse samples from 149 HIV-positive and 88 HIV-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 45 publications
8
37
0
1
Order By: Relevance
“…However, it is noteworthy that while we focused mainly on oral-related variables in this study, the list of included variables is not exhaustive and has likely missed variables that might explain the variation of the microbiomes, such as fat-free mass ( 7 ) and flossing habit ( 5 ). In agreement with our findings, a study on the oral mycobiome of a population comprising HIV-positive and HIV-negative individuals based on ITS2 sequencing has identified sex as a significant variable affecting the oral mycobiome, with brushing frequency, mouthwash usage, frequency of alcoholic beverage intake, and frequency of oral sex being some of the insignificant variables ( 31 ). However, in contrast to our findings, the oral mycobiome in that study was also affected by caries status and missing teeth, and not by gingivitis and diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it is noteworthy that while we focused mainly on oral-related variables in this study, the list of included variables is not exhaustive and has likely missed variables that might explain the variation of the microbiomes, such as fat-free mass ( 7 ) and flossing habit ( 5 ). In agreement with our findings, a study on the oral mycobiome of a population comprising HIV-positive and HIV-negative individuals based on ITS2 sequencing has identified sex as a significant variable affecting the oral mycobiome, with brushing frequency, mouthwash usage, frequency of alcoholic beverage intake, and frequency of oral sex being some of the insignificant variables ( 31 ). However, in contrast to our findings, the oral mycobiome in that study was also affected by caries status and missing teeth, and not by gingivitis and diet.…”
Section: Discussionsupporting
confidence: 91%
“…Zakaria et al ( 30 ) studied the salivary mycobiome in a healthy Japanese population of community-dwelling elderly and revealed the dominance of Candida albicans in most samples. Candida is also reported to be the predominant genus in the oral mycobiome of an American population comprising HIV-positive and HIV-negative individuals ( 31 ). The dominance of Candida in the oral mycobiome was also observed in our population, indicating its importance as a major member of the healthy oral mycobiome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most abundant fungi in HIV-uninfected controls were Candida , Pichia , and Fusarium , presenting in 58%, 33%, and 33%, respectively. [ 67 ] Fidel et al [ 68 ] have also demonstrated the relative abundance of oral fungal communities in 149 HIV-positive and 88 HIV-negative subjects. This study suggested that 168 species can be identified in 12 dominant genera by sequencing of the ITS2 region of the rRNA gene repeat.…”
Section: The Alterations In the Oral Microbiome In Hiv Infectionmentioning
confidence: 99%
“…Several oral diseases often occur in PLWH, including periodontal diseases, OPC, oral warts, oral hairy leukoplakia, and Kaposi sarcoma (KS), even in those receiving ART. [44] Globally Fidel et al [68] 149 HIV+ subjects 88 HIVÀ subjects…”
Section: Effects Of the Oral Microbiome On Hiv-associated Oral Diseasesmentioning
confidence: 99%
“…Colonization of C. albicans and C. dubliniensis are the most prominent taxa observed in high abundance in saliva of HIV infected individuals. While incidence of oral candidiasis typically declines after HAART initiation, recent evidence suggests that the impact of HIV/HAART on the mycobiome is modest but not more considerable than other factors such as sex ( 105 ).…”
Section: Oral Microbiome In Hivmentioning
confidence: 99%